PRINCIPLES OF WASTE MANAGEMENT: PROBLEMS AND SOLUTIONS - Anatolij Ryzhenkov (Гуманитарные и юридические исследования)
This article argues that in a complex environmental situation in the sphere of production and consumption waste management the legislator pays particular attention not only to the formulation of legal rules to solve this problem, but the special principles aimed at establishing the kernel of this legal institution, establishing its development priorities for the long term. Depending on the role in structuring law, Russian scientists distinguish substitutional, institutional, sub-sectoral, sectoral, cross-sectoral and general legal principles of law. The article proposes to fix the main organizing principle in production and consumption waste management - waste prevention principle. This is due to the fact that complete realization of the principles of waste production and consumption is hampered not only by objective reasons (lack of funds for waste collection in the local budget), but also drawbacks of the economic model that prevailed not only in Russia but also in most countries of the world. This principle should mean that the main direction of the ecological policy of the state is not just "treatment of symptoms", but the adoption a long-term programme of action aimed at changing the current economic model and the reduction of the amount of arising waste. Such transition is possible only in conditions of international cooperation as well as changes in consumer behavior patterns, which is possible only in case of reforming the priorities of the existing system of environmental education.